ANALISIS MOTIVASI BELAJAR SISWA SEKOLAH DASAR DALAM PEMBELAJARAN DARING DI DESA SADANG SELAMA PANDEMI COVID-19 - Mursyidah - Mursyidah; Moh Kanzunnudin; Sekar Dwi Ardianti (Jurnal Prasasti Ilmu, 2021)
The purpose of conducting this research is to find out the students’ motivation in online learning process, to find out the problems faced by the student, parents, and teachers and described the effective solution for the problems in Sadang. The researcher used descriptive qualitative in conducting this research. The technique in collecting data, the researcher used documentation, observation, and interview. The result of this research shows that students’ have a good motivation in learning process in the first condition, but gradually they feel bored and saturated. The problems faced by the teachers is about the difficulties to give the material, the learning process is not effective because teachers can not directly give explanation of the material to the students, teachers get difficulties to build a good motivation in learning process. The problems faced by the parents is about helping students to study, finished the homework, and worried about the students’ psychology progress. the researcher believed that every problems will have an alternative solution.  By inviting students to discuss together about the material and created kind of study group with other students can make the students excited to study. Have a good communication and collaboration with parents is the appropriate solution for all of the teachers’ problems, teachers can discuss about the learning progress, and monitoring the students by parents. Teachers should have variative way in learning process to created students’ creativity. The solution for parents is help students during learning process and invite them to play together, it will make them excited to study.